What is the role of profibrogenic and proinflammatory factors in developing atrial fibrillation associated with metabolic syndrome components? - V. A. Ionin; E. I. Barashkova; V. A. Pavlova; G. I. Borisov; K. A. Averchenko; E. L. Zaslavskaya; E. I. Baranova (Российский кардиологический журнал)
Aim. To determine the concentration of blood fibrotic and inflammatory biomarkers in patients with atrial fibrillation (AF) associated with metabolic syndrome (MS) components.Material and methods. The study included 646 patients aged 35-65 years: patients with AF and MS (n=142), those with AF and without MS (n=113), those with MS and without AF (n=175) and the control group consisted of healthy subjects without cardiovascular and metabolic diseases (n=107). All participants underwent anthropometric and laboratory investigations. Profibrogenic (aldosterone, galectin-3, TGF-beta1, CTGF) and proinflammatory (CT-1, IL-6) factors were determined in serum and plasma by ELISA. Statistical analysis was performed using IBM SPSS Statistics software (version 22.0).Results. The highest concentrations of fibrotic and inflammatory biomarkers were found in patients with AF in combination with MS. In MS patients without AF, the concentration of aldosterone, galectin-3, TGF-beta1, CTGF, CT-1, and IL-6 was also higher than in healthy subjects. The levels of aldosterone, CT-1 and IL-6 in patients with AF were higher in the presence of three or more MS components, while the highest values of these parameters were found in patients with five MS components. The lowest concentrations of galectin-3, CTGF, and CT-1 in patients with AF were found in patients without MS components, and in the presence of even 1 MS component, they were significantly higher. Correlation analysis made it possible to establish a stronger relationship between aldosterone and TGF-betal with systolic blood pressure (p=0,493, p<O,O001 and p=0,530, p<O,O001), and CT-1, CTGF and IL-6 in a greater degree correlated with waist circumference (p=0,563, p<0,0001; p=0,626, p<0,0001; p=0,480, p<O,O001). The concentrations of galectin-3 and CTGF were more positively correlated with an increase in the number of MS components. In patients with AF and hypertension (HTN), but without abdominal obesity (AO), higher values of aldosterone (108,1±70,3 pg/ml and 89,3±32,2 pg/ml, p=0,003) and TGF-beta1 (3680,1±1863,3 pg/ml and 1968,1±1611,5 pg/ml, p=0,015) in serum than in AF patients without HTN and without AO. In the group of patients with AF and AO, but without HTN, higher concentrations of IL-6 (2,9±0,7 pg/ml and 1,9±0,6 pg/ml, p=0,001) and CTGF (162,9±92,2 pg/ml and 116,3±63,4 pg/ml, p=0,0001).Conclusion. It can be assumed that hypertension through the aldosterone system and TGF-beta1, as well as abdominal obesity through the cytokine system CT-1 and IL-6 activate various mechanisms and pathways for myocardial remodeling. Integral molecules galectin-3 and CTGF mediate their interactions, in particular in patients with a combination of several MS components and contribute to a higher AF risk.